Endoplasmic reticulum acetyltransferases Atase1 and Atase2 differentially regulate reticulophagy, macroautophagy and cellular acetyl-CoA metabolism - Michael J. Rigby (Nature Portfolio, 2021)
Rigby et al. use transgenic mice that are deficient in the endoplasmic reticulum acetyltransferases Atase1 or Atase2 to demonstrate the differential role of these enzymes in the regulation of reticulophagy and macroautophagy. Their study emphasizes ATase1 as a potential translational target for diseases characterized by toxic protein aggregation in the secretory pathway.